Trk retrograde signaling requires persistent, Pincher-directed endosomes - Philippidou, Polyxeni (National Academy of Sciences, 2011)
Target-derived neurotrophins use retrogradely transported Trk-signaling endosomes to promote survival and neuronal phenotype at the soma. Despite their critical role in neurotrophin signaling, the nature and molecular composition of these endosomes remain largely unknown, the result of an inability to specifically identify the retrograde signaling entity. Using EGF-bound nanoparticles and chimeric, EGF-binding TrkB receptors, we elucidate Trk-endosomal events involving their formation, processing, retrograde transport, and somal signaling in sympathetic neurons. By comparing retrograde endosomal signaling by Trk to the related but poorly neuromodulatory EGF-receptor, we find that Trk and EGF-receptor endosomes are formed and processed by distinct mechanisms. Surprisingly, Trk and EGF-receptors are both retrogradely transported to the soma in multivesicular bodies. However, only the Trk-multivesicular bodies rely on Pincher-dependent macroendocytosis and processing. Retrograde signaling through Pincher-generated Trk-multivesicular bodies is distinctively refractory to signal termination by lysosomal processing, resulting in sustained somal signaling and neuronal gene expression.